Brand Image Of Toyota Sparepart At Lampung Service Workshop As Customer Choice - Fauzi Efendi; Vethy Octaviani; Sapta Sari (Perkumpulan Dosen Muda (PDM) Bengkulu, 2022)
The use of spare parts increases every year. The spare part brand recommended by Lampung Service Workshopprovides a workshop warranty. The workshop provides a guarantee on the recommended spare parts on the grounds that the workshop does not want to experience loss of service or material, this is also related to the image of Lampung Service Workshop if the workshop has dared to guarantee a spare part will give a positive image. This study aims to describe the Brand Image of Toyota Spare Parts at Lampung Service Workshop as Customer Choice. This research uses qualitative research with data collection techniques of observation, interviews and documentation and research informants 5 people who are workshop owners, mechanics and consumers. The theoretical basis used in this research is the Elements of Brand Image according to Kerby in Sandy (2010; 22) which include Resilience, Conformity, Accuracy, and Connotation. The results showed that: first, the resilience (Tenacity). Relating to the quality and brand image of the product itself. the durability of Toyota products is superior to other brands, only in terms of price, Toyota is slightly more expensive than other products, customers of Lampung service workshops know the durability of Toyota products based on the user's personal experience and explanations from the workshop itself. Second, the conformity of the Toyota brand with consumer needs and expectations. The suitability felt by consumers varies, ranging from the suitability of price with quality, conformity with the delivery of the workshop owner, and conformity with the durability of the product itself. Third, thoroughness: Toyota brand accurately and consistently in accordance with the quality and information conveyed, in addition to the Toyota brand the price offered in every place must be consistent or the same. There are no similarities between the Toyota brand and other brands, so Toyota can be said to be more chosen by customers than other brands. Fourth, connotation: Products with the Toyota brand are more in demand than other brand products, this is because Toyota products are considered to be more able to meet the needs of consumers!customers because in terms of prices they are more affordable, product durability is more durable, easy to obtain and environmentallyfriendly..